Behavior change intervention targeting physical activity and diet improves stress and sleep - Samuel L. Battalio; Bonnie Spring; Elizabeth Wilson; Donald Hedeker; Angela Fidler Pfammatter (PLoS ONE, 2026)
Background Poor diet, low physical activity, high stress, and poor sleep are prevalent modifiable risk factors for chronic diseases. Synergistic effects of interventions targeting diet and activity on other health risk behaviors such as stress and sleep are understudied. Purpose To conduct a secondary data analysis to investigate whether interventions targeting diet and activity produce collateral improvements in stress and sleep. Methods Make Better Choices 2 was a randomized clinical trial to test a technology-assisted coaching intervention with modest incentives to improve diet and activity, as compared to a matched intervention targeting improved stress and sleep. Participants (n = 212) were adults (76.4% female, 59% non-white minority, mean age = 40.8 years) with multiple diet and activity risk behaviors. For 7 days at baseline, 3-, 6-, and 9-months, participants reported perceived sleep duration, stress, diet, and activity through a smartphone application. Outcomes were evaluated by linear mixed models. The study was registered on clinicaltrials.gov (NCT01249989) . Results Both interventions produced significant, statistically comparable improvements in average daily stress rating (z = 1.35, p = .177). Reduction in average daily stress rating was 1.68 following diet/activity intervention (z = −12.25, P < .001) and 2.08 following stress/sleep intervention (z = −7.83, P < .001) on an 11-point Likert scale. Though changes in sleep duration for both groups were clinically meaningful, the stress/sleep intervention produced statistically larger improvements in sleep as compared to the diet/activity intervention (z = −3.79, P < .001). Sleep duration increased 26.39 minutes following diet/activity intervention (z = 3.16, P = 0.002) and 92.65 minutes following stress/sleep intervention (z = 5.912, P < 0.001). Conclusions Findings suggest that diet and activity behavior change interventions can effectively improve outcomes within and between the behavior domains they directly target. Future research should identify common mechanistic pathways to inform development of interventions that efficiently change multiple health behaviors implicated in chronic disease morbidity and mortality.